Clinical features and prognostic factors related to mortality in hospitalized adult patients with COVID-19 in a public hospital in Lima, Peru - Mejía, Fernando (2020)
The COVID-19 pandemic has deeply affected the national health system in Peru, and despite the many strategies implemented to control the epidemic, the collapse of the sanitary system was imminent. We performed a retrospective cohort from the clinical records of adult patients with COVID-19 admitted in Hospital Cayetano Heredia (Lima, Peru), between March and June 2020. A total of 369 patient charts were included for analysis; 241 (65.31%) were male and the median age was 59 years (IQR: 49-68). Most patients (68.56%) reported at least one comorbidity; more frequently: obesity (42.55%), diabetes mellitus (21.95%), and hypertension (21.68%). The median duration of symptoms prior to hospital admission was 7 days (IQR: 5-10). Reported in-hospital mortality was 49.59%. By multiple Cox regression, oxygen saturation (SaO2) level at admission was the main predictor of patient mortality, with SaO2 levels of 84-80% and <80% had 4.44 (95%CI 2.46-8.02) and 7.74 (95%CI 4.54-13.19) times greater risk of death, respectively, when compared to patients with SaO2 >90%. Additionally, older age (>60 years old) was associated with 1.9 times greater mortality. Our study finds SaO2 at admission and older age to be independent predictors of in-hospital mortality. These findings suggest a delay in early detection of hypoxemia in the community, therefore, we propose the implementation of monitoring for hypoxemia among outpatients with COVID-19 as well as appropriate and timely oxygen therapy in admission.